PELAKSANAAN PERJANJIAN SEWA MENYEWA ANTARA PENYEWA DENGAN PEMILIK RUMAH DI DESA KAPUR KOMPLEK GRAHA KAPUR KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - - A1012131004, YULIANA MONIKA (Jurnal Hukum Prodi Ilmu Hukum Fakultas Hukum Untan (Jurnal Mahasiswa S1 Fakultas Hukum) Universitas Tanjungpura, 2017)
As is the case in general agreement, the lease agreement that occurred at the time of the achievement of an agreement between the parties to a lease agreement. The lease agreement that was made legally must comply with Article 1320 of the Code of Civil Code so that both parties are bound to implement the agreement. The formulation of the problem in this thesis research is "Do Homeowners Have Implement Lease Agreement Home With Tenant House in the village of Lime Complex Graha Kapur Kubu Raya In accordance with the Agreement?" This research was conducted by the method of empirical research that examines the revealed facts objectively as found in the research field. That the owner of the house in the village of Lime Complex Graha Kapur Kubu Raya has not yet executed a lease agreement houses The factors that led to the owner's home village of Lime Complex Graha Kapur Kubu Raya has not yet executed a lease agreement homes to tenants because they offer them a higher price than another tenant and the homeowner negligent regarding when the expiration of the lease the leased house. The legal consequences against the homeowner who has not executed a lease agreement on the tenant house, is the homeowner can be charged payment for damages As for efforts to be made by the tenant against the owner of the house has not yet executed a lease agreement on a tenant house was completed amicably and demanded adequate compensation to the owner of the house. However, the tenant is never to take legal actions in the form of a lawsuit in the District Court, as a tenant claims settlement until today resolved amicably Â  Keyword: Lease agreement, Homeowners, Renters